Exploring the importance of teaching phrasal verbs to enhance communicative competence in university students - Boylan Durán, Ana Gisselle (2024)
This research project investigated the professors’ perspectives and experiences in teaching phrasal verbs to university students from Universidad Estatal Península de Santa Elena, where English is a foreign language not commonly used in daily life. The objective was to explore effective methods for teaching phrasal verbs to enhance students' communicative competence. This study employed a qualitative research approach and open-ended interviews with university professors to understand their challenges and perspectives on teaching phrasal verbs. The results indicated that professors encountered significant difficulties due to the complex nature of phrasal verbs and the limited exposure students have to English outside the classroom. The findings suggested that innovative teaching methods, including explicit instruction and contextualized practice, can improve students' understanding and usage of phrasal verbs. The conclusions highlighted the need for integrating phrasal verbs more effectively into the university curriculum to support students' academic success and future career opportunities.